2021
DOI: 10.1155/2021/5555218
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Blunt Trauma Analysis during a Frontal Impact

Abstract: The aorta is the largest artery of the human body, and it is considered in the continuous medium mechanics as a hyperelastic material for its biological properties. The thoracic aorta is directly affected in vehicular collision events by compression generated between the ribcage and the three-point seatbelt tension producing injuries in the artery wall. A three-dimensional model of the thoracic aorta was constructed from digital tomographic images considering the ascending aorta, the aortic arch, and the desce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Standard trauma protocol at Rajaie Cardiovascular Medical and Research Center limits the resolution and slice interval of CT images; as a result, it was not possible to capture wall of the aorta for this study. In a previous study of Aortic Blunt Trauma, a simple model of aortic wall with constant thickness along aorta was used 24 . Furthermore, it has been reported that although aortic wall thickness varies significantly in the population 59 , values of less than 4 mm is considered normal 60 , thus 1.5 mm thickness was chosen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard trauma protocol at Rajaie Cardiovascular Medical and Research Center limits the resolution and slice interval of CT images; as a result, it was not possible to capture wall of the aorta for this study. In a previous study of Aortic Blunt Trauma, a simple model of aortic wall with constant thickness along aorta was used 24 . Furthermore, it has been reported that although aortic wall thickness varies significantly in the population 59 , values of less than 4 mm is considered normal 60 , thus 1.5 mm thickness was chosen.…”
Section: Methodsmentioning
confidence: 99%
“…In agreement with previous study others showed that max stress occurs in the isthmus region. It was also concluded that comparing the stretching that occurs at the ascending aorta to the bending generated at the aortic arch, bending is a leading factor in BTAR 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%